2011
DOI: 10.1002/fld.2606
|View full text |Cite
|
Sign up to set email alerts
|

Reduced‐order modeling based on POD of a parabolized Navier–Stokes equation model I: forward model

Abstract: SUMMARYA proper orthogonal decomposition (POD)-based reduced-order model of the parabolized Navier-Stokes (PNS) equations is derived in this article. A space-marching finite difference method with time relaxation is used to obtain the solution of this problem, from which snapshots are obtained to generate the POD basis functions used to construct the reduced-order model. In order to improve the accuracy and the stability of the reduced-order model in the presence of a high Reynolds number, we applied a Sobolev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 27 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…A unique aspect of this method is that the snapshot data is formed from the solution vectors containing angular coefficients. In addition these vectors are recorded through space, as opposed to time, and it is this approach that allows for time independent problems to be solved (which is similar to that of [23,24]). It has been shown that the angular discretised system of equations derived from the POD formulation can be constructed very efficiently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique aspect of this method is that the snapshot data is formed from the solution vectors containing angular coefficients. In addition these vectors are recorded through space, as opposed to time, and it is this approach that allows for time independent problems to be solved (which is similar to that of [23,24]). It has been shown that the angular discretised system of equations derived from the POD formulation can be constructed very efficiently.…”
Section: Resultsmentioning
confidence: 99%
“…(6). As no time dimension is available in which to take the snapshots, the set of snapshots are formed by recording these moments at different positions in space -in essence this work has interchanged the roles of space and time in standard POD, with angle and space, respectively (for similar techniques see [23,24]). The snapshots of angular moments are taken at each node defined by the full model's mesh.…”
Section: The Pod Angular Discretisationmentioning
confidence: 99%
“…This method has been used to establish some POD-based reduced-order Galerkin, FE, and FD numerical models for PDEs (see [7,9,12,15,16,17,18]). Moreover, it has played an important role in the reduced-basis of numerical models for PDEs (see [10,19,21,24,25]).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is also important to note that this approach has similarities with that of [27], which solved the two dimensional time independent parabolized Navier-Stokes equation. In this previous work snapshots were constructed by solving the problem using one of the spatial dimensions as though it were time.…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to the shallow water equations [24], the Euler equations [25], the full Navier Stokes equations [26] and the various reduced versions of it, e.g. the parabolized Navier Stokes [27,28].…”
Section: Introductionmentioning
confidence: 99%